PRAKTIK JUAL BELI IKAN DAN PROBLEMATIKA PENAKARANNYA DI PASAR SAYANG-SAYANG PERSPEKTIF HUKUM EKONOMI SYARIAH - Fitria Hariyanti; Muhammad Dimas Hidayatullah Wildan (Universitas Islam Negeri Mataram, 2024)
This research was motivated by the large number of traders at the Sayang- Sayang market who sell fish but some of them still do not fulfill the terms and conditions of buying and selling. Such as reducing the weight of fish scales so that one party suffers a loss because they are not honest in their buying and selling transactions. The focus studied in this thesis is (1) What are the factors that cause sellers to cheat in fish buying and selling measurements? (2) How does sharia economic law review the practice of buying and selling fish? The type of research used in this research uses qualitative research. The data collection methods used were observation, interviews and documentation. The analytical method used is qualitative analysis in the form of data reduction, data display, and drawing conclusions. The results of the research show (1) The factors that cause traders to cheat in buying and selling fish using a measuring system are lack of knowledge and understanding regarding appropriate scales, lack of socialization from the government, lack of public awareness of the role of religious figures regarding scales that are in accordance with Islamic law. (2) the practice of buying and selling fish using this measuring system partially meets the requirements for legal buying and selling. However, there are also some who have not fulfilled it. One of the buying and selling conditions that has not been fully fulfilled in the practice of buying and selling fish using this measuring system is the lack of clarity in the goods being traded in terms of substance, form and level.